2012
DOI: 10.7854/jpsk.2012.21.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the Central Ogcheon Belt, Korea

Abstract: The tectonic evolution of the Central Ogcheon Belt has been newly analyzed in this paper from the detailed geological maps by lithofacies classification, the development processes of geological structures, microstructures, and the time-relationship between deformation and metamorphism in the Ogcheon, Cheongsan, Mungyeong Buunnyeong, Busan areas, Korea and the fossil and radiometric age data of the Ogcheon Supergroup(OSG). The 1st tectonic phase(D*) is marked by the rifting of the original Gyeonggi Massif into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…Cluzel et al [64,65] divided the Ogcheon Metamorphic Belt into five main tectonic units bounded by thrusts: Iwharyeong, Poeun, Turungsan, Chungju, and Pibanryeong units. Although there has been some controversy regarding deformation stages and the exact timing of metamorphism, it has been suggested that bimodal volcanisms and sedimentation in the rift setting occurred from the Neoproterozoic [67,[74][75][76][77] to late Paleozoic [78,79], followed by the subsequent Permian to Triassic tectonic event that extensively affected the Ogcheon Metamorphic Belt, forming the southeastward stacking of the nappes [64,65,67,72,79,80]. [67,84].…”
Section: Geological Setting and Outcrop Descriptionmentioning
confidence: 99%
“…Cluzel et al [64,65] divided the Ogcheon Metamorphic Belt into five main tectonic units bounded by thrusts: Iwharyeong, Poeun, Turungsan, Chungju, and Pibanryeong units. Although there has been some controversy regarding deformation stages and the exact timing of metamorphism, it has been suggested that bimodal volcanisms and sedimentation in the rift setting occurred from the Neoproterozoic [67,[74][75][76][77] to late Paleozoic [78,79], followed by the subsequent Permian to Triassic tectonic event that extensively affected the Ogcheon Metamorphic Belt, forming the southeastward stacking of the nappes [64,65,67,72,79,80]. [67,84].…”
Section: Geological Setting and Outcrop Descriptionmentioning
confidence: 99%
“…더 나아가 금강 석회암이 신원생대의 눈덩어리 지구(Snowball Earth) 에 수반된 빙하 기원의 덮개 탄산염암(cap carbonate) 으로 해석된 바 있다 (Choi et al, 2012). 금강휴게소 부근에는 1:5만 옥천도폭 (Kim et al, 1978)에 잘 기술된 바와 같이 금강석회암이 함력천매 암으로 구성된 황강리층과 암회색-흑색의 점판암과 천 매암으로 주로 구성된 변성이질암층[명오리층 (Lee et al, 1998b;Choi et al, 2012;Choi, 2014) 또는 창리층 (Kim et al, 1978;Kang et al, 2012)으로 불림] 사이에 존재한다 (Fig. 1c) (Fig.…”
Section: 서 론 화석이 발견되지 않거나 드문 쇄설성(변성)퇴적암 의 연대측정 및 근원지 해석을 위한 대안으로 고분해 unclassified
“…영암의 은적-상은 광화대 지역은 지구조적으로 옥 천대의 남서단부에 위치하며 (Kang and Lee, 2002;Kang et al, 2012), 백악기의 화산활동에 의한 목포-해남-영암 환상구조대의 북동부에 위치하고 있다( (Kim, 1991;Kim and Nagao, 1992), 환상구조의 내부에 존재하는 화강암이 백악기가 아닌 쥐라기로 알려져, 콜드론 내 관입한 것이 아니라 쥐라기 산이 화 강암의 돔이 이들 연변에 퇴적한 백악기 지층의 기반 암으로 제시한 바 있다 (Koh, 1996;Koh and Chang, 1996). 조사지역인 상은-은적 광화대 일대의 지질은 유문 암질 응회암, 안산암질 응회암, 각력질 응회암, 유문 암 및 석영반암 등으로 구분한 경우 (Choi, 1987;Kim, 1989;Yun, 1989;Kim et al, 1990Kim et al, , 1991와 함화산력유문암질 응회암, 석영안산반암, 안산암, 석 영반암 등으로 구분한 경우 (Lee et al, 1996)와 함께 백악기 유천층군 화원층 내의 서호 응회암으로 기재 된 바 있다 (Koh, 1996;Koh and Chang, 1996).…”
Section: 지 질unclassified